Equity valuation of Burberry Group Plc - Pardal, Maria Ana Marques Moreira da Costa (2021)
The purpose of this dissertation is to determine Burberry’s price per share as of 31st of March 2021. Based on the current share price, an investment recommendation was issued. The valuation was supported by a current macroeconomic analysis, an industry overview, the company’s business strategy and past financial performance. The share price was obtained through the combination of two valuation methods: the Discounted Cash Flow method and the Relative Valuation method. The valuation was then stressed through an alternative scenario analysis and a sensitivity analysis to acknowledge the uncertainty in the market. In the end, a price of £19.96 is achieved. When comparing with the share price as of 11th December 2020, a Hold recommendation is issued, with a potential upside of 10%.